2018
DOI: 10.2147/ott.s172717
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of apatinib treatment for gastric cancer, hepatocellular carcinoma and non-small cell lung cancer: a meta-analysis

Abstract: Apatinib (Aitan®, brand name in China) is a new anti-antiangiogenic agent that has recently been approved for the treatment of advanced gastric cancer (GC) in China. Nevertheless, its therapeutic efficacy against other types of advanced solid tumors remains unclear. This meta-analysis examines the short-term efficacy and safety of apatinib or combination therapy for GC, hepatocellular carcinoma (HCC) and non-small-cell lung cancer (NSCLC); and provides a discussion of its anti-angiogenesis therapy applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 22 publications
3
36
2
Order By: Relevance
“…This study focuses on the in‐vitro and in‐vivo investigations on the pharmacokinetic interactions between a herbal product HSYW and apatinib, a newly approved TKI that is used to treat advanced‐stage gastric cancer in China with the recommended dosage of 850 mg for adult patients. [ 10 ] In clinical settings, patients with advanced‐stage gastric cancer are frequently administered with multiple medications (including some herbal medicines), and thus, the potential herb–drug interactions should be investigated extensively. Notably, HSYW, an herbal product developed in the 1990s, has been frequently used in combination with apatinib for the treatment of patients with advanced‐stage gastric cancer in several Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study focuses on the in‐vitro and in‐vivo investigations on the pharmacokinetic interactions between a herbal product HSYW and apatinib, a newly approved TKI that is used to treat advanced‐stage gastric cancer in China with the recommended dosage of 850 mg for adult patients. [ 10 ] In clinical settings, patients with advanced‐stage gastric cancer are frequently administered with multiple medications (including some herbal medicines), and thus, the potential herb–drug interactions should be investigated extensively. Notably, HSYW, an herbal product developed in the 1990s, has been frequently used in combination with apatinib for the treatment of patients with advanced‐stage gastric cancer in several Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The incubation system included potassium phosphate buffer (pH 7.4, 100 m m ), apatinib (2.0 μ m , final concentration), HLM (0.2 mg/ml, final concentration) or RLM (0.2 mg/ml, final concentration), and NADPH‐generating system, as reported previously. [ 9–10 ] Before inhibition assays, the formation of two oxidative metabolites of apatinib was validated in the linear range of reaction time and microsomal protein concentration. In brief, HSYW (0.2555 mg dried materials/ml to 7.9835 mg dried materials/ml, final concentration) was added to the incubation system for 10 min pre‐incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Camrelizumab (SHR-1210) is an anti-PD-1 antibody, which in combination with Apatinib, a TKI, has been reported at the ASCO 2018 meeting in a phase I trial with 18 HCC patients to demonstrate a response rate of 38.9% and a median progression free survival of 7.2 months (NCT02942329) [60] .…”
Section: Camrelizumab (Anti-pd-1) + Apatinib (Tki)mentioning
confidence: 99%
“…14 Several papers indicated that apatinib was an appropriate choice for chemo-refractory malignancies. [15][16][17] Although some papers have demonstrated that apatinib was effective and safe for advanced or metastatic gastric cancer, breast cancer, ovarian cancer, lung cancer, and liver cancer, 13,14,[18][19][20][21][22] doubts still exist about whether it is an appropriate choice for patients with advanced cervical cancer. Therefore, the aim of this retrospective study was to assess the efficacy and safety of apatinib in advanced cervical cancer patients with ≥2 lines of chemotherapy failure.…”
Section: Introductionmentioning
confidence: 99%